2018
DOI: 10.1017/s1368980018003233
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sources of salt intake in adults and older people: a population-based study in a Brazilian town

Abstract: ObjectiveTo assess salt intake and its dietary sources using biochemical and self-report methods and to characterize salt intake according to sociodemographic and disease-related variables in a sample of the Brazilian population.DesignPopulation-based cross-sectional survey.SettingSalt intake was assessed by biochemical (24 h urinary Na excretion) and self-report methods (sodium FFQ, 24 h dietary recall, seasoned-salt questionnaire, discretionary-salt questionnaire and total reported salt intake).ParticipantsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 56 publications
(69 reference statements)
1
24
0
5
Order By: Relevance
“…The meta-analysis included 12 studies published since 2010 (29,875 people), [9,11,12,14,15,19,[21][22][23] with a mean age ranging from 41.2 to 53.5 years [14,23]; the proportion of men varied between 33.7% and 48.2% [11,23]. The proportion of people with hypertension went from 17.0% to 52.5% (Table 1) [11,22].…”
Section: Quantitative Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The meta-analysis included 12 studies published since 2010 (29,875 people), [9,11,12,14,15,19,[21][22][23] with a mean age ranging from 41.2 to 53.5 years [14,23]; the proportion of men varied between 33.7% and 48.2% [11,23]. The proportion of people with hypertension went from 17.0% to 52.5% (Table 1) [11,22].…”
Section: Quantitative Synthesis Of Resultsmentioning
confidence: 99%
“…The random effects meta-analysis including studies published since 2010 revealed a pooled mean estimates 24 h sodium consumption of 4.13 g/day (95% confidence interval: 3.82-4.44, I 2 : 99.7%) [9,11,12,14,15,19,[21][22][23], which will be equivalent to 10.49 g/day of salt.…”
Section: Quantitative Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations